A fertility needs assessment survey of male cancer patients. Issue 12 (2nd October 2018) - Perez, Samara; Lambert, Sylvie D.; Lee, Virginia; Loiselle, Carmen G.; Chan, Peter; Gupta, Abha; Lo, Kirk; Rosberger, Zeev; Zelkowitz, Phyllis
Abstract: Objective: To describe fertility‐related informational needs and practices, and to examine if demographic characteristics are related to these needs and practices. Methods: A needs assessment survey was conducted at three Canadian cancer centres. Results: 192 male cancer patients ( M age = 33.6) completed the survey. Most patients (70%) recalled having had a discussion with a health care provider regarding their fertility and 44% banked their sperm. Patients reported not getting all the information that they wanted, eg, the risk that a future child may have the same type of cancer (78%), and what was covered by insurance plans (71%). Barriers to sperm preservation were urgency to begin cancer treatment (49%), not planning to have a child in the future (47%) and worries that cancer could be passed on to future children (38%). Participants' age and being the parent of a child were significantly associated with having had a discussion about fertility. Participants' age, province, being the parent of a child and the desire for future children were significantly associated with fertility preservation. Conclusions: Discussions with health care providers were more frequent, and fertility preservation rates were higher than in past studies, but still not all patients' questions were answered. Misconceptions about passing on cancer to one's child, and that sperm preservation will delay treatment, should be dispelled. Health care providers can ask patients if they have any desire to have children in the future as a way to initiate a discussion of fertility preservation. Key information gaps and psychosocial resource needs are suggested to fully meet male cancer patients' fertility‐related concerns.